Prospect for measurements of (γ, n) reaction cross-sections of p-nuclei at ELI-NP - Söderström, P.-A.; Kuşoğlu, A.; Testov, D. (Frontiers in Astronomy and Space Sciences, 2023)
The gamma beam system under construction at the ELI-NP facility in Romania is projected to give the nuclear physics community access to an experimental system providing a high-intensity, narrow bandwidth photon beam at variable energy. With high-efficiency detector systems in place, the experimental programme will have a strong potential for in-depth studies of rare stable isotopes originating from the astrophysical p-process. In particular, the neutron detection systems are already implemented through a dedicated 3 He long neutron counter array, called ELIGANT-TN, that is completed and in use. In this mini-review, we will give a summary of the current status of existing (γ, n) cross-section data, as well as the methods to obtain them, and highlight the future potential to expand and improve such data using the ELI-NP instrumentation and beam-lines.